S4.5a A randomized, double blind phase II proof-of-concept superiority trial of fosravuconazole 200 mg or 300 mg weekly dose versus itraconazole 400 mg daily, all three arms in combination with surgery, in patients with eumycetoma in Sudan—top line results. (20th September 2022) - Fahal, Ahmed Hassan; Bakhiet, Sahar Mubarak; Mohamed, El Samani Wadaa; Ahmed, Eiman Siddig; Bakhiet, Osama El Hadi; Yousif, Abu Bakar Ahmed; Fahal, Lamis Ahmed; Alla, Hadel Yassir Atta; Razig, A Razig Osman A; Siddig, Emmanuel Edwar; Hassan, Omnia Babekir; Abdulla, Sahar A Rahman; et al.
Abstract: Objectives: To determine whether, in addition to surgery, fosravuconazole (Fos) monotherapy of either 200 mg or 300 mg weekly was more effective [defined as complete cure at the End of Treatment (EOT; 52-week) visit] than the standard-of-care 12-month regimen of itraconazole (Itra) monotherapy, in patients with small to moderate eumycetoma lesions caused by Madurella mycetomatis. Methods: This was a single-center (Mycetoma Research Center, Khartoum, Sudan), comparative, randomized, double-blind, parallel-group, active-controlled, clinical superiority trial in participants with eumycetoma requiring surgery. Participants were randomized in a 1:1:1 ratio. In Arm 1 participants took a loading dose of Fos 300 mg on Day 1, Day 2, and Day 3, followed by a weekly dose of 300 mg for a total duration of 12 months. In Arm 2 participants took Fos 200 mg on Day 1, Day 2, and Day 3, followed by a weekly dose of 200 mg for a total duration of 12 months. In Arm 3 participants took Itra 400 mg daily for 12 months. All patients underwent surgery after 6 months of treatment in which the remaining lesion was removed. Mycetoma lesions were between 2 to ≤16 cm in diameter. The age cut-off was ≥15 years. The diagnosis of M. mycetomatis was confirmed by PCR. Safety monitoring included, among other, severe, and serious treatment-related events. Results: A total of 122 participants were screened and 104 participants were enrolled (34 in Fos 300 mg, 34 in Fos 200 mg weekly, and 36 in Itra 400 mg). Complete cure after 12 months (EOT) of treatment was demonstrated in terms of an absence of eumycetoma mass, sinuses, and discharge; normal ultrasound of the lesion site or normal MRI; and a negative fungal culture from a surgical biopsy if a mycetoma mass was present. The complete cure rate was assessed in the mITT population. Secondary efficacy analyses were performed in the Per Protocol population. In addition, the influence of age, changes in clinical symptoms and signs, size, and duration of the lesion on outcome was examined. Safety was satisfactory and compliance was good. Conclusion: This is the first randomized controlled trial in eumycetoma, comparing two azoles, fosravuconazole (two dosage regimens) and itraconazole, in combination with surgery. Detailed efficacy and safety results will be communicated and discussed in the oral presentation.